Spectrum-Effect Relationship Analysis of Bioactive Compounds in Zanthoxylum nitidum (Roxb.) DC. by Ultra-High Performance Liquid Chromatography Mass Spectrometry Coupled With Comprehensive Filtering Approaches - Rao, Si-wei; Duan, Yuan-yuan; Pang, Han-qing; Xu, Shao-hua; Hu, Shou-qian; Cheng, Ke-guang; Liang, Dong; Shi, Wei (Frontiers in Pharmacology, 2022)
Zanthoxylum nitidum (Roxb.) DC. (ZN), with strong effects of anti-inflammation and antioxidant activities is treated as a core herb in traditional Chinese medicines (TCMs) preparation for treating stomachache, toothache, and rheumatoid arthritis. However, the active ingredients of ZN are not fully clarified due to its chemical complexity. In the present study, a double spectrum-effect analysis strategy was developed and applied to explore the bioactive components in herbs, and ZN was used as an example. Here, the chemical components in ZN were rapidly and comprehensively profiled based on the mass defect filtering-based structure classification (MDFSC) and diagnostic fragment-ion-based extension (DFIBE) approaches. Further, the fingerprints of 20 batches of ZN samples were performed by high performance liquid chromatography (HPLC), the anti-inflammatory and antioxidant activities of the 20 batches of ZN samples were conducted. Finally, the partial least squares regression (PLSR), grey relational analysis (GRA) models and Spearman’s rank correlation coefficient (SRCC) were applied to discover the bioactive compounds in ZN. As a result, a total of 48 compounds were identified or tentatively characterized in ZN, including 35 alkaloids, 7 coumarins, 3 phenolic acids, 2 flavonoids, and 1 lignan. The results achieved by three prediction models indicated that peaks 4, 12, and 17 were the potential anti-inflammatory compounds in ZN, whereas peaks 3, 5, 7, 12 and 13 involved in the antioxidant activity. Among them, peaks 4, 5, 7 and 12 were identified as nitidine, chelerythrine, hesperidin and oxynitidine by comparison with the standards and other references. The data in current study achieved by double spectrum-effect analysis strategy had great importance to improve the quality standardization of ZN, and the method might be an efficiency tool for the discovery of active components in complex system, such as TCMs.